THE EFFECT OF STORAGE TIME OF LONG-TAILED CHICKEN CEMENT WITH EGG YOLK AND COCONUT WATER DILUTED AT A TEMPERATURE OF 5oC - Enji, Dyah Risma Aprilia; Bebas, Wayan; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana, 2023)
Long-tailed chickens or commonly called onagadori chickens are classified as rare and endangered animals. This ornamental chicken has the advantage of its long tail reaching 10 meters. This study aims to determine the effect of storing semen with egg yolk coconut water diluent stored at cold temperatures on motility, abnormalities and viability. The design in this study used a completely randomized design (CRD) with 7 treatment groups for storage duration, namely 0 hours, 12 hours, 24 hours, 26 hours, 48 hours, 60 hours, 72 hours. The research object used was male long-tailed chickens that were sexually mature at the age of 6-8 months. Chicken semen storage technique by massaging the chicken's back (massage). Semen examination was carried out macroscopically and microscopically. Viability and abnormality of spermatozoa were observed using the eosin negrosin staining method. This study concluded that the motility, viability and spermatozoa abnormalities of long-tailed chickens in egg yolk coconut water diluent could be maintained for 48 hours at 5°C storage temperature with 52.41% motility, 50.15% viability and 7.33% abnormality. In order to obtain optimal results in supporting the success of artificial insemination, long-tailed chicken semen with egg yolk diluent and coconut water should not be stored for more than 60 hours.